PENGEMBANGAN MODEL DEEP LEARNING UNTUK DETEKSI SUARA MENGGUNAKAN CONVOLUTIONAL NEURAL NETWORK - NORITA SINAGA; Imam Riadi; Herman (LPPM Universitas Abdurrab, 2026)
Sound detection and keyword recognition in audio signals have become rapidly growing research areas due to their wide range of applications, from intelligent audio surveillance to human-computer interaction systems. This study aims to develop a deep learning model based on Convolutional Neural Networks (CNN) to automatically detect and classify specific words in speech recordings. The focus of this research is the detection of the keywords